2018
DOI: 10.1051/cagri/2018008
|View full text |Cite
|
Sign up to set email alerts
|

Transfert en cadmium et zinc vers l’orge de printemps en sols contaminés et non contaminés de Belgique : évaluation et prédiction

Abstract: En Région wallonne, des sols agricoles situés à proximité d’anciens sites de traitements de minerais ont été impactés par des retombées atmosphériques contaminées en cadmium (Cd), plomb (Pb) et zinc (Zn). Afin d’étudier l’impact de ces contaminations sur la qualité des productions agricoles, une étude du transfert en Cd et Zn du sol vers l’orge de printemps (Hordeum vulgare L.) a été réalisée sur une de ces zones contaminées. Dix-huit prélèvements d’orges ont été effectués en zone contaminée, 10 autres en zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Porosity (∅) and void ratio (e) were calculated from bulk density (Bd) assuming an average mineral density of 2.65 g cm −3 [56]. pH of the water was measured by potentiometry [57].…”
Section: Soil Measurementmentioning
confidence: 99%
“…Porosity (∅) and void ratio (e) were calculated from bulk density (Bd) assuming an average mineral density of 2.65 g cm −3 [56]. pH of the water was measured by potentiometry [57].…”
Section: Soil Measurementmentioning
confidence: 99%
“… 17 19 . To minimize Cd bioaccumulation in plants, it has been reported that Zinc which is an important micronutrient could play this role 20 , 21 . This positive role of Zn was due to its competitive ion for Cd absorption from the soil with the help of their chemical similarity 2 .…”
Section: Introductionmentioning
confidence: 99%